Upper-body resistance training following soccer match play: Compatible, complementary, or contraindicated? - Sabag, A.; Lovell, R.; Walsh, N. P.; Grantham, N.; Lacome, M.; Buchheit, M. (International Journal of Sports Physiology and Performance, 2021)
Purpose: During heavily congested schedules, professional soccer players can experience exacerbated fatigue responses, which are thought to contribute to an increased risk of injury. Given that match-induced residual fatigue can last up to 72 hours, many coaches naturally prioritize recovery in the days immediately following match day. While it is intuitive for coaches and training staff to decrease the amount of auxiliary training practices to focus on recovery, prescribing upper-body resistance training on the day after match play has recently emerged as a specific training modality in this context. While these sessions may be implemented to increase training stimulus, there are limited data available regarding the efficacy of such a practice to improve recovery kinetics. Methods: In this narrative review, the authors look at the theoretical implications of performing upper-body resistance training on the day after match play on the status of various physiological and psychological systems, including neuromuscular, metabolic, hormonal, perceptual, and immunological recovery. Results: The available evidence suggests that in most cases this practice, as currently implemented (ie, low volume, low intensity), is unlikely to be complementary (ie, does not accelerate recovery) but is potentially compatible (ie, does not impair recovery). Conclusion: Overall, because the perception of such sessions may be player dependent, their programming requires an individualized approach and should take into account match dynamics (eg, fixture scheduling, playing time, travel).